Pengaruh Penggunaan Permainan Ludo Kimia sebagai Media Pembelajaran Materi Asam dan Basa terhadap Hasil Belajar Peserta Didik Fase F SMA/MA - Widya Rahayu Putri; Iswendi Iswendi (ALSYS, 2025)
This study was motivated by the availability of the Ludo Kimia educational game, which has been proven valid, practical, and effective as a learning exercise on acid-base material, yet its impact on students' cognitive learning outcomes remains unexplored. The objective of this research is to analyze the effect of using the Ludo Kimia game on the cognitive learning outcomes of Phase F students at SMA Negeri 14 Padang. The study employed a quasi-experimental method using the Pretest-Posttest Control Group Design. The population consisted of all Phase F students, with samples selected through simple random sampling, resulting in class XI F.4 as the control group and XI F.3 as the experimental group. The instrument used was a multiple-choice test comprising 20 validated items. Data were analyzed using the t-test to evaluate the research hypothesis. The results showed that the average posttest score of the experimental class was 86.56, higher than the control class average of 77.5. The t-test yielded tcount (2.466) > ttable (1.996) at a significance level of α = 0.05, indicating a statistically significant effect. The study concludes that the use of the Ludo Kimia game significantly improves students’ cognitive learning outcomes on acid-base topics.